The Struggle of Sinden: Female Artists, Family Economy, and Religious Identity in Art - Bayu Tri Cahya; Waluyo; Ratih Paramitasari; Sekar Rani Salsabila (IBDA` : Jurnal Kajian Islam dan Budaya, 2025)
This study aims to analyze the role, contribution, and convergence of the Sinden (traditional female singer) profession in strengthening the family economy while navigating the challenges of religious identity in Solo, Central Java. This study uses a qualitative approach with an interpretive paradigm and a phenomenological approach. The data collection technique uses in-depth interviews with active Sinden informants with dual roles as housewives and artists. The results of the study indicate that the economic contribution of the head of the family includes the role of an economic safety valve, household financial manager, and teamwork builder in the family. The study also reveals a convergence between religious beliefs and their profession, as Sinden. Despite the ambiguity of this profession in religious communities, primarily due to stage performances that do not strictly adhere to Islamic guidelines, Sinden consistently upholds standards of modesty, religious principles, and their dignity as Muslim women. This study contributes to providing an overview of the dualism of women's roles in the context of Javanese-Islamic culture, which adds insight into the complex interactions between gender, economy, art, and religion in the lives of contemporary traditional societies.